A comprehensive analysis of the efficacy and effectiveness of COVID-19 vaccines - He, Xiaofeng; Su, Jiao; Ma, Yu’nan; Zhang, Wenping; Tang, Shixing (Frontiers in Immunology, 2022)
It is urgently needed to update the comprehensive analysis about the efficacy or effectiveness of COVID-19 vaccines especially during the COVID-19 pandemic caused by SARS-CoV-2 Delta and Omicron variants. In general, the current COVID-19 vaccines showed a cumulative efficacy of 66.4%, 79.7%, and 93.6% to prevent SARS-CoV-2 infection, symptomatic COVID-19, and severe COVID-19, respectively, but could not prevent asymptomatic infection of SARS-CoV-2. Furthermore, the current COVID-19 vaccines could effectively prevent COVID-19 caused by Delta variant although the incidence of breakthrough infection of SARS-CoV-2 Delta variant increased when the intervals post full vaccination extended, suggesting the waning effectiveness of COVID-19 vaccines. In addition, one dose booster immunization showed an effectiveness of 74.5% to prevent COVID-19 caused by Delta variant. However, the current COVID-19 vaccines could not prevent infection of Omicron sub-lineage BA.1.1.529, and was about 50% effectiveness to prevent COVID-19 caused by Omicron sub-lineage BA.1.1.529. Furthermore, the effectiveness was 87.6% and 90.1% to prevent severe COVID-19 and COVID-19-related death caused by Omicron sub-lineage BA.2, respectively while one dose booster immunization could enhance the effectiveness of COVID-19 vaccines to prevent the infection and COVID-19 caused by Omicron sub-lineage BA.1.1.529 and sub-lineage BA.2. Two doses booster immunization showed an increased effectiveness of 81.8% against severe COVID-19 caused by Omicron sub-lineage BA.1.1.529 variant comparing with one dose booster immunization. The effectiveness of the booster immunization with RNA-based vaccine BNT162b2 or mRNA-1273 was over 75% against severe COVID-19 more than 17 weeks after booster immunization whereas the heterogenous booster immunization showed better effectiveness than homologous booster immunization. In summary, the current COVID-19 vaccines could effectively protect COVID-19 caused by Delta and Omicron variants, but was less effective against Omicron variant infection. One dose booster immunization could enhance protection capability and two doses booster immunization could provide additional protection against severe COVID-19.